Obstacle avoidance for kinematically redundant manipulators in dynamically varying environments - Klein, Charles A., author; Maciejewski, Anthony A., author; SAGE Publications, publisher (Colorado State University. Libraries, 1985)
The vast majority of work to date concerned with obstacle avoidance for manipulators has dealt with task descriptionsin the form of pick-and-place movements. The added flexibility in motion control for manipulators possessing redundant degrees of freedom permits the consideration of obstacleavoidance in the context of a specified end-effector trajectory as the task description. Such a task definition is a more accurate model for such tasks as spray paintingor arc welding.The approach presented here is to determine the required joint angle rates for the manipulator under the constraints of multiple goals, the primary goal described by thespecified end-effector trajectory and secondary goals describing the obstacle avoidance criteria. The decomposition of the solution into a particular and a homogeneous componenteffectively illustrates the priority of the multiple goals that is exact end-effector control with redundant degrees of freedom maximizing the distance to obstacles. An efficient numericalimplementation of the technique permits sufficiently fast cycle times to deal with dynamic environments.
Keywords: kinematically redundant manipulators; obstacle avoidance